Pensions and Wages: A Test for Equalizing Differences - Schiller, Bradley R.; Weiss, Randall D. (The Review of Economics and Statistics, 1980)
T HE Employee Retirement Income Security Act of 1974 (ERISA) has provoked considerable debate about the desirability of various retirement plan provisions and the appropriate role of government in regulating the private pension plan contract. Among the issues debated is the question of who presently pays for private retirement benefits, and who should. An answer to at least the first of these questions is provided by the theory of differences. In competitive markets, a firm that provides pension benefits should pay lower wages than one that does not, thereby offering the same equilibrium value of total compensation to all workers of equal productivity. By the same token, firms that offer pension benefits on relatively desirable terms are expected to offer lower wage rates than firms offering pension benefits on very restricted terms. These simple notions imply that (1) workers pay for their own pensions by accepting lower wages, and (2) government regulation of the content of private pension plans may not significantly alter labor costs or the expected lifetime income of workers. From this perspective, contributions to private pension plans serve the exclusive purpose of enabling individuals to reallocate their resources over time according to their diverse tastes, and do not affect total labor compensation. The primary purpose of this paper is to examine the empirical validity of the equalizing differences hypothesis. By examining the relationship between wages and pension plans, we also hope to improve our ability to account for wage differentials. Contributions to private retirement plans have grown rapidly in recent years-from 1.7% to nearly 4.0% of private sector wages between 1950 and 1979, and coverage has increased from 22% to more than 45% of all private wage and salary workers.' Most previous studies of wage determination have ignored fringe benefits, let alone pension plans.2 But if the growth of pension plans continues and the equalizing differences hypothesis is correct, continuing neglect of pension provisions implies an increasing inability to account for wage differentials across firms, industries, occupations, race, sex, and age, or by the same token, an increasing tendency to attribute such differences to the wrong factors. The paper begins by reviewing the properties of competitive equilibriuni in labor markets in which compensation consists of current and deferred wages.3 Building on this foundation, we demonstrate how the annual cost of a pension plan depends on its various provisions, including vesting, early retirement, normal retirement, and benefit formula. With data on the earnings and pension provisions of individual workers in 133 large firms, we find some support for the equalizing differences hypothesis. We also observe that the extent of equalization diminishes with age, suggesting a redistribution of compensation from younger to older workers.